Ocular biological parameters and prevalence of myopia in vocational high school and general high school in China - Liu, Yang; Meng, Dexin; Wang, Yun; Wang, Xuechun; Xue, Caihong; Hao, Rui; Zhang, Wei (Frontiers in Public Health, 2023)
Significance Higher prevalence of myopia is possibly associated with more extended schooling schedules. Therefore, adjustments to high school curricula may aid in reducing the prevalence of myopia among adolescents. Purpose To investigate the prevalence of myopia among 15- to 18-year-old adolescents in Tianjin, China, and to evaluate the impact of different educational schedules on the prevalence of myopia among high school students. Methods This is a school-based epidemiological study with a cross-sectional design. Ocular biological parameters and noncycloplegic photorefraction were examined using optical biometry devices and photoscreener devices. Each student’s spherical equivalent (SE) and ocular biometry were recorded, and the prevalence of myopia was calculated. Results A total of 2,867 participants (1,519 males and 1,348 females) were tested for non-cycloplegic refraction, axial length (AL), central corneal thickness (CCT), anterior chamber depth (ACD) and lens thickness (LT). In this research, the overall prevalence of myopia was 81.6%, with high myopia accounting for 11.8%. Myopia prevalence was substantially higher in general high schools than in vocational high schools, with 86.1 and 70.1%, respectively. There were no significant differences in the prevalence of myopia (p = 0.744) or high myopia (p = 0.851) across the three vocational school years. In the general high school, however, there was an increase of 4.6% (p < 0.05) in myopia prevalence between year 10 and year12. Conclusion Comparing vocational and standard high school students, there are considerable disparities in prevalence of myopia, spherical equivalent, and ocular biological parameters. The prevalence of myopia and high myopia increased among standard high school students, but remained relatively consistent among students in vocational schools.